2017
DOI: 10.1111/are.13505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of guanidinoacetic acid supplementation in all-plant protein diets on growth, antioxidant capacity and muscle energy metabolism of bullfrogRana(Lithobates)catesbeiana

Abstract: Effects of guanidinoacetic acid (GAA) supplementation in all-plant protein diets were evaluated on growth, antioxidant capacity and muscle energy metabolism of Rana (Lithobates) catesbeiana. Six diets were prepared: a basal fish meal diet (FM), an all soybean meal diet (SM) and four GAA-supplemented diets by adding 0.2, 0.4, 0.6 and 0.8 g GAA/kg to the SM diet (GAA2, GAA4, GAA6 and GAA8 diets). Triplicate groups of bullfrog (45 AE 0.2 g) were fed the diets to apparent satiation for 8 weeks.Total substitution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…This is similar to observations reported for other animals. For example, supplementing 0.4 g GDA/kg to the diet significantly improved bullfrog growth performance; however, a further increment of dietary GDA resulted in significant reduction in growth performance (Zeng, Rahimnejad, & Wang, ). The effective and safe dosage of GDA as a dietary additive for broiler chickens has been suggested to be lower than 0.6–0.8 g/kg of diet by the European Food Safety Authority ().…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to observations reported for other animals. For example, supplementing 0.4 g GDA/kg to the diet significantly improved bullfrog growth performance; however, a further increment of dietary GDA resulted in significant reduction in growth performance (Zeng, Rahimnejad, & Wang, ). The effective and safe dosage of GDA as a dietary additive for broiler chickens has been suggested to be lower than 0.6–0.8 g/kg of diet by the European Food Safety Authority ().…”
Section: Discussionmentioning
confidence: 99%
“…Guanidinoacetic acid (GAA), which is synthesized from the glycine and arginine in the kidney, is the nature precursor of creatine 3,4 . Supplementation with GAA can spare the endogenous synthesis of GAA by arginine and glycine; thus more arginine and glycine can be used for the synthesis of proteins or endogenous amino acids to promote the growth of the body 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al. (2018) reported that dietary supplementation of 0.4 g GAA/kg to the SM diet significantly improved the growth performance of bullfrog. Fu et al.…”
Section: Discussionmentioning
confidence: 99%